Travailler avec l'arbre qui saigne - Eduardo Di Deus (Revue d'anthropologie des connaissances, 2023)
Natural Rubber production in Brazil is mostly associated with the extraction of latex from “wild” rubber trees in the Amazon rainforest. However, almost half of the country's natural rubber production comes from numerous rubber plantations (Hevea brasiliensis) in the north-western region of the State of São Paulo. The tapping of rubber trees is a manual activity at the heart of an agricultural sector attached to industry, in particular the tire industry. This seemingly simple activity requires a high level of technical skill from the tapper, since the accuracy of his incisions on the tree determines the profitability and longevity of the plantation. In this article the objective is to highlight how tappers work with rubber trees in plantations in São Paulo, Brazil and to characterize their working relationships with these trees from the perspective of the ethnography of techniques, a methodological journey capable of to show the mediations between humans and plants in the context of agricultural work.